Improving Dribbling Learning Outcomes in Basketball Games Through Lecture Plus Demonstration and Practice Methods for Grade XI Students of SMA Negeri 9 Ambon - Efendi, Efendi; Rumahlewang, E; Matitaputty, J. (Peneliti.net, 2024)
This classroom action research was carried out with the aim of finding out the improvement in learning outcomes of basic dribbling techniques in the game of basketball among class From the results of the research carried out, there was an increase in student learning outcomes from the initial conditions of cycles I and II, both from an increase in the average value of learning basic dribbling techniques in the game of basketball and the completeness value of learning outcomes. In the initial conditions, only 15 students (65%) had completed the expected KKM, namely 75, while 5 students were still below the KKM. The increase in movement ability in learning basic dribbling techniques in basketball games through the CPDL method (lecture plus demonstration and practice), can be seen from the KKM score (75) after taking action in cycle I, the student's completed learning score was 15 out of 20 (65%) and in cycle II, 20 out of 20 students completed the total or 100% completion.